Introspección e informes verbales en procesamiento humano de información - Froufé Torres, Manuel (1985)
The goal of this paper is to review the research work and the theories that are based on verbal reports and to reflect on the introspective value of verbal reports in relation to the processing functions, from a cognitive point of view. To this purpose this article reviews every research work that questions the role of conciousness in the process and as a product of human thinking through an external communication.